PENGARUH PROGRAM EXPERIENTIAL MARKETING TERHADAP PEMBENTUKAN BRAND IDENTITY BLIND CAFE : Survei pada konsumen yang Berkunjung ke Blind Cafe - Maya Rosmaya, - (2009)
Maya Rosmaya, The Influence of Experiential Marketing Program toward Blind Cafe's Brand Identity (Survey On consumer of visitor Blind Cafe). Paper, 2009, supervised by Dr. Ratih Hurriyati, M.Si and Gitasiswhara, SE., Par., MM The Role of F&B business (Resto and Cafe) give a big market opportunity widely, so that many restaurant and café was built as tourism component. Bandung is one of city which is famous in food and beverage industry. It offers distinctive facilities by offering an interesting Product and Service. Blind café is one of cafés in Bandung that focus and include in the competition so that this cafe has to have features. Blind Cafe wants to be the first café in Indonesia that offer the best place to have a dine in the darkness. So that in 2007 Blind Cafe had got MURI reward as the most unique restaurant by offering the darkness concept. By providing experiential marketing can build Blind Cafe's brand identity. Based on the explanation above, the research about the influence of experiential marketing toward brand identity by applying marketing management approach, especially about experiential marketing and brand identity. Type of This research is descriptive verificative with 100 respondents wich is use explanatory survey with systematic random sampling technique. SPSS 16,0 as additional software to back up all data through Analysis technique using regression. Based on hypothesis test, experiential marketing has an influence toward brand identity,it means that if experiential marketing is better, so Blind Cafe brand identity is higher too.